2018
DOI: 10.1155/2018/6707291
|View full text |Cite
|
Sign up to set email alerts
|

Delusions in Patients with Dementia with Lewy Bodies and the Associated Factors

Abstract: Objective Delusions are common neuropsychiatric symptoms in patients with dementia with Lewy bodies (DLB). The aim of this study was to investigate the associated factors of delusions in patients with DLB. Method A retrospective study of outpatients with DLB registered in a regional hospital's database was performed. The associated factors including cognitive performance, clinical features, vascular risk factors, and neuropsychiatric symptoms between delusional and nondelusional patients with DLB were compared… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
9
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 36 publications
(53 reference statements)
3
9
0
1
Order By: Relevance
“…A cross-sectional and retrospective study of 1025 patients with dementia in Spain found that delusion and hallucinations were more prevalent in DLB patients than those with AD and PDD [ 23 ]. In a recent comparative study of 207 delusional and nondelusional patients with DLB, the authors concluded that the delusional patients had poorer cognitive function and more severe neuropsychiatric symptoms [ 24 ]. In a cross-sectional study, 21 DLB and 35 PDD patients with recurrent visual hallucinations were evaluated.…”
Section: Methodsmentioning
confidence: 99%
“…A cross-sectional and retrospective study of 1025 patients with dementia in Spain found that delusion and hallucinations were more prevalent in DLB patients than those with AD and PDD [ 23 ]. In a recent comparative study of 207 delusional and nondelusional patients with DLB, the authors concluded that the delusional patients had poorer cognitive function and more severe neuropsychiatric symptoms [ 24 ]. In a cross-sectional study, 21 DLB and 35 PDD patients with recurrent visual hallucinations were evaluated.…”
Section: Methodsmentioning
confidence: 99%
“…Phantom boarder phenomenon and paranoid ideation were the most common delusion in these disorders. Finally, it has been shown that patients with DLB who presented delusions have higher disease severity, more neuropsychiatric symptoms and are more cognitively impaired ( 58 ). Frequent and distressing delusions in DLB have been associated with higher caregiver burden and with worse patient's quality of life compared with patients with other neurodegenerative disorders ( 58 ).…”
Section: Delusions In Neurodegenerative Disordersmentioning
confidence: 99%
“…20 Common delusions observed in patients with DLB include misidentification delusions (52.4%), delusions of others stealing (35.3%), delusions of danger to self (21.3%), and delusions of spousal infidelity (7.2%). 21,22 Of the misidentification delusion subtype, the most common delusions are house misidentification, Capgras delusions (belief that someone familiar has been replaced by an imposter), and reduplicative amnesia (belief that a place has been duplicated and is present in 2 locations simultaneously). Delusions and greater cognitive decline have been associated in DLB.…”
Section: Dementia With Lewy Bodiesmentioning
confidence: 99%